REKRUTMEN SUMBER DAYA MANUSIA - Riska Awaliyah; Khoiruddin; Rizky Fadillah; Tuti Andriani (CV. ADIBA AISHA AMIRA, 2025)
Human resource (HR) recruitment is an important aspect of HR management that aims to obtain workers that are in accordance with the needs of the organization. An effective recruitment process ensures that the organization has individuals who are competent, committed, and able to contribute to achieving goals. In the era of globalization and tight competition, recruitment strategies must continue to be adjusted to technological developments and labor market dynamics.This article discusses the concept of HR recruitment, including the stages and methods that can be applied in the recruitment process. Various recruitment methods, both internal and external, have their own advantages and challenges that need to be adjusted to the needs of the organization. In addition, the use of technology in the recruitment process, such as artificial intelligence (AI) and online recruitment applications, further increases the efficiency of candidate selection. A deep understanding of recruitment will help organizations increase their effectiveness in obtaining quality workers. With the right strategy, organizations can create a productive work environment, increase competitiveness, and ensure long-term growth.